Fan - N - Pick Technique Towards Students’ Motivation In Reading Comprehension At FPBS IKIP Mataram - Imran, Fathurrahman; Aprianoto, Aprianoto (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2020)
This research aims to know the Fan-N-Pick technique towards students’ motivation in reading comprehension. This research is quantitative research with experimental design. The respondends are 40 students which is divided into two groups are experimental and control class. The data is analyzed using descriptive and inferential statistics. The result shows that ttes (4.810) is higher than that of ttable (1.671) in confidence level of 0.05 and the degree of freedom is 70. It can be concluded that there is significant effect of Fan-N-Pick technique towards students’ motivation in reading comprehension.